Exvotos y retablitos Religión popular y comunicación social en México - Jorge A. González (Estudios sobre las Culturas Contemporáneas)
The study of social comniunication in our societies has given much attention to understanding MEDIA instead of understanding COMiMUNICATION. That means to construct its relationships with cultures, ideologies, social classes and linking with the structuring, consolidation, crisis and de/structuring of the social consensus. The author, introduces the "CULTURAL FRONTS" category to study and specific scale, that being the points of contact and confrontation between cultures of several classes in a given society: spaces for the fundamental struggle of tlie processes of the social construction of sense. Social communication is always something more than just tlie collective diffusion media. The article proposes a descriptive study of "retablitos" and votive offerings of various mexican popular sanctuaries from which a possible tlieoretical and methodological itinerary, having both varied repercussions in the analysis of cultural diversity and the media cultural work, is suggested. The votive offering appears then as a popular communication instrument which allows the reconstruction of some aspects of the ideological battle for the legitimacy of the competence to "define" the social world.